2001
DOI: 10.1108/00070700110382911
|View full text |Cite
|
Sign up to set email alerts
|

Measuring consumer quality judgements

Abstract: Many on-farm-processed products frequently command a premium price, characterised as they are by unique sensory properties and image. Examines the nature of consumer judgements about product quality for farmhouse Cheddar cheeses based on utilities derived from the product attributes, and the trade-off against price. Determines key Cheddar cheese attributes through in-depth interviews with specialist cheese consumers and employs conjoint analysis to estimate the utilities associated with these attributes based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 18 publications
2
58
0
4
Order By: Relevance
“…These findings are in agreement with the results of Kupiec (2001) and Glenn Wells (1994), both of whom identified flavour as an important attribute to cheese consumers. Glenn Wells (1994) also reported freshness to be important among the consumers surveyed.…”
Section: Consumer Perceptions Of Cheese Qualitysupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are in agreement with the results of Kupiec (2001) and Glenn Wells (1994), both of whom identified flavour as an important attribute to cheese consumers. Glenn Wells (1994) also reported freshness to be important among the consumers surveyed.…”
Section: Consumer Perceptions Of Cheese Qualitysupporting
confidence: 94%
“…Kupiec (2001) conducted a study of farmhouse cheese in Edinburgh, Glasgow and Aberdeen. He identified the following four criteria to assess quality of cheese.…”
Section: Cheese Studiesmentioning
confidence: 99%
“…The product attributes and their possible levels were selected on the basis of the results of two focus groups (n = 16; 8 members per session), data from literature 11,20,26 as well as from the results of a preliminary sensory study which identified sensory properties of NAB beers on sale in Italy (QDA techniques and sensory mapping). The attributes studied included product features such as colour and flavour, marketing mix variables such as price attribution, and structural characteristics such as packaging and general claims.…”
Section: Methodsmentioning
confidence: 99%
“…The stimuli or the raw material for a conjoint measurement study comprises single, stand-alone elements. These elements of phrases are combined with other phrases to form a concept [ 59 ] , enabling a number of products to be compared and ranked based on their attributes [60][61][62] . For example, the developer might decide to incorporate certain ingredients with known health bene fi ts or create the product under a speci fi ed brand name [ 63 ] .…”
Section: Expectations and Acceptability Of Diabetic And Reduced-calormentioning
confidence: 99%